Fatores e mecanismos associados à inovação incremental em processos no ambiente industrial: o caso da Café Iguaçu - Fontanini, José Italo Candêo (2005)
The technological innovation has been more and more present in the global world. Particularly in the case of Brazil, it is taking part of the globalization process with a more relevant part of its innovation being done in the process area. This specific kind of innovation has some relation with the narrow range of products diversification and the relative low level of technology incorporation associated with the Brazilian industries. The comprehension and systematization of the most contributive factors related to the incremental innovation in processes may be relevant towards the improvement and intensification of the innovative process, thereby improving the general performance and results of these organizations and also the country. The specific aim of this study was the systematization of the incremental innovation in processes in an industrial environment. With this purpose, the identification of the most relevant factors, its contribution and validation amongst a set of pre implemented innovation was done. This systematization of the incremental innovation in processes was unfolded in a case study performed at Companhia Iguaçu de Café Solúvel - Café Iguaçu, a company located in Cornélio Procópio, north of Paraná state. This company is an important instant coffee Brazilian manufacturer with a business profile in beverages and food sectors and with a characteristic aspect in dealing mainly with incremental innovation in its processes. The methodological procedures applied were composed by participative observation, consult of the company records and documents, a questionnaire and an interview. The questionnaire was organized in 23 factors judged by 15 employees that decided the importance of each one, based on a Likert scale. The semi-structured interview was made with 6 employees. A final workshop to validate the study was made with the interviewed employees. The systematic presented, has a logical and chronological factors integration and activities to facilitate and guide the development of the incremental technological innovation in processes in an industrial environment. Among the main factors that underscore the study are the creativity, the motivation, the facilitators, the knowledge transfer and the results recognition. Even considering that the results of this study can not be generalized, the systematic herewith presented may be of interest to other studies and further development of products innovation in departments other than the production one. It may also be of interest to other companies in the seeking to improve competitively through innovations.